Photodynamic Therapy of Presumed Choroidal Metastasis Secondary to Colorectal Carcinoma: Literature Review - Laurentino Biccas Neto; José Z. Pulido; Gustavo B. Melo; Luiz H. Lima; Eduardo B. Rodrigues (Case Reports in Ophthalmological Medicine)
Colorectal cancer may yield metastasis to the choroid. Its management may be challenging, since there is no consensus about treatment. We describe a case of a 70-year-old male with colon cancer who complained of worsening visual acuity of his better-seeing eye to 20/40 secondary to a nonpigmented choroidal mass of medium reflectivity under the inferior temporal arcade and neurosensory foveal detachment. Besides systemic chemotherapy, local treatment with verteporfin photodynamic therapy (vPDT) was performed. After one month, visual acuity improved to 20/25 and subretinal fluid faded. In conclusion, vPDT may be a useful adjuvant treatment modality for choroidal metastasis secondary to colorectal cancer.